Simulations of sea urchin early development delineate the role of oriented cell division in the morula-to-blastula transition. (June 2020) - Bodenstein, Lawrence
Abstract: The sea urchin morula to blastula transition has long been thought to require oriented cell divisions and blastomere adherence to the enveloping hyaline layer. In a computer simulation model, cell divisions constrained by a surface plane division rule are adequate to effect morphological transition. The hyaline membrane acts as an enhancer but is not essential. The model is consistent with the orientation of micromere divisions and the open blastulae of direct developing species. The surface plane division rule precedes overt epithelization of surface cells and acts to organize the developing epithelium. It is a universal feature of early metazoan development and simulations of non-echinoid cleavage patterns support its role throughout Metazoa. The surface plane division rule requires only local cues and cells need not reference global positional information or embryonic axes. Highlights: The cleavage stage sea urchin embryo is examined in a computer simulation model. A surface plane division rule drives the sea urchin morula-to-blastula transition. The hyaline layer is not necessary for blastocoel development in the sea urchin. The surface plane division rule effect is independent of the early cleavage pattern. The surface plane division rule underlies metazoan blasula formation.